Symbol of Communication between Worship Leader and Music Priest in Maintaining Harmonization of Worship Music at GBI Lembang Bandung - Sugiarta, Nugraha; Hanafi, Hanafi; Amos, Amos (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Music has an important role in Christian worship. Harmonious music is solemnity if the Worship leader and musician church can carry out their duties properly. Worship leader and musician communicate using symbols when leading worship. This research aims to determine how the meaning of the communication symbols of church music groups in maintaining the harmonization of worship music. This research uses qualitative method with a symbolic interaction study approach. Data was collected through observation, interviews and documentation. The informant determination technique used is purposive sampling.. The results of the study found 2 parts of the symbol. Namely song map and keytone. The song map symbol is a part of a song element that is used when the music is already running and is given when the musical verse is about to end, with the aim of bridging every movement of the musical verse. Keytone symbols are used to align the chords. The language used verbally and nonverbally. The key tone is used by worship leaders to music priests, and music priests to one another. The music priest has a dominant role according to the symbol of the song map. The keyboardist has a role on the cooling down section, guitarist on interlude, drums on full music and overtones. Worship leaders and music priests must have spiritual criteria as pulpit ministers, because spiritual criteria are the main key to be good to God.